Silicon Nanowires - Uda, Hashim, Prof. Dr.; Mohammad Nuzaihan, Md Nor; Nur Hamidah, Abdul Halim (AFAG Messen & Ausstellungen GmbH, 2010)
Prof. Dr. Uda Hashim and his team won gold at International Trade for Ideas - Inventions - New Products Exhibition (IENA 2007) organized by AFAG Messen & Ausstellungen GmbH was held at Nuremberg, Germany on 1st - 4th November 2007.